Three-dimensional wavelet coding of video with global motion compensation - Chou, Philip A.; Mehrotra, Sanjeev; Wang, Albert; Xiong, Zixiang; Chou, Philip A. (Data Compression Conf., 1999)
Three-dimensional (2D+T) wavelet coding of video using SPIHT has been shown to outperform standard predictive video coders on complex high-motion sequences, and is competitive with standard predictive video coders on simple low-motion sequences. However, on a number of typical moderate-motion sequences characterized by largely rigid motions, 3D SPIHT performs several dB worse than motion-compensated predictive coders, because it is does not take advantage of the real physical motion underlying the scene. We introduce global motion compensation for 3D subband video coders, and find 0.5 to 2 dB gain on sequences with dominant background motion. Our approach is a hybrid of video coding based on sprites, or mosaics, and subband coding.